2016
DOI: 10.3389/fncel.2016.00048
|View full text |Cite
|
Sign up to set email alerts
|

Reelin-Related Disturbances in Depression: Implications for Translational Studies

Abstract: The finding that reelin expression is significantly decreased in mood and psychotic disorders, together with evidence that reelin can regulate key aspects of hippocampal plasticity in the adult brain, brought our research group and others to study the possible role of reelin in the pathogenesis of depression. This review describes recent progress on this topic using an animal model of depression that makes use of repeated corticosterone (CORT) injections. This methodology produces depression-like symptoms in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 142 publications
(165 reference statements)
0
27
0
Order By: Relevance
“…Further evidence suggest that it is the dorsal hippocampus that is involved in spatial learning and memory, while the ventral hippocampus is more associated with limbic functions (Brooker, Gobeske, Chen, Peng, & Kessler, ; Hyer, Hunter, Katakam, Wolz, & Glasper, ; Kheirbek & Hen, ; Loxton & Canales, ; McHugh, Fillenz, Lowry, Rawlins, & Bannerman, ; Schoenfeld, McCausland, Sonti, & Cameron, ). Abnormalities in hippocampal function are associated with various neurological and psychiatric disorders in adults such as anxiety, schizophrenia and depression (Ampuero, Jury, Hartel, Marzolo, & Zundert, ; Brooker et al, ; Caruncho et al, ; Danzer, Kotloski, Walter, Hughes, & McNamara, ; Liu et al, ; Perez‐Domper et al, ; Yun et al, ).…”
Section: Locations Of Adult Neural Stem Cells In the Mammalian Brainmentioning
confidence: 99%
See 3 more Smart Citations
“…Further evidence suggest that it is the dorsal hippocampus that is involved in spatial learning and memory, while the ventral hippocampus is more associated with limbic functions (Brooker, Gobeske, Chen, Peng, & Kessler, ; Hyer, Hunter, Katakam, Wolz, & Glasper, ; Kheirbek & Hen, ; Loxton & Canales, ; McHugh, Fillenz, Lowry, Rawlins, & Bannerman, ; Schoenfeld, McCausland, Sonti, & Cameron, ). Abnormalities in hippocampal function are associated with various neurological and psychiatric disorders in adults such as anxiety, schizophrenia and depression (Ampuero, Jury, Hartel, Marzolo, & Zundert, ; Brooker et al, ; Caruncho et al, ; Danzer, Kotloski, Walter, Hughes, & McNamara, ; Liu et al, ; Perez‐Domper et al, ; Yun et al, ).…”
Section: Locations Of Adult Neural Stem Cells In the Mammalian Brainmentioning
confidence: 99%
“…Additional genes are newly expressed at this stage of maturation (Gonçalves et al, ), including brain‐derived neurotrophic factor (BDNF), Reelin, cAMP response element‐binding protein (CREB) and possibly activation protein transcription factor (AP‐1). Reelin, an extracellular glycoprotein, is highly expressed in hippocampal cells, both during development and in adult hippocampal GABAergic interneurons of many different species (Ampuero et al, ; Caruncho et al, ). Reelin influences many different aspects of hippocampal neurogenesis including neuronal fate and migration, the formation of dendritic spines and final integration of granule neurons into the hippocampal circuitry (Ampuero et al, ; Caruncho et al, ).…”
Section: Differentiation and Maturation—type‐3 Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced Reln mRNA and protein levels have been observed in postmortem brain regions of patients with schizophrenia and bipolar disorder, but not with major depression (Fatemi et al, ; Folsom & Fatemi, ; Guidotti et al, ). However, deficits in Reln expression have been also reported in animal models of depression (Caruncho et al, ). Interestingly, a recent study reported that blocking the Reln signaling pathway increases dendritic growth and branching in adult neurons, which is in contrast with previous studies showing that deficiency in Reln signaling impairs dendritic development (Ampuero et al, ).…”
Section: Discussionmentioning
confidence: 98%